Thermal emission in the successive orders of scattering (SOS) radiative transfer approach. (November 2022) - Herreras-Giralda, M.; Litvinov, P.; Dubovik, O.; Derimian, Y.; Lapyonok, T.; Fuertes, D.; Sourdeval, O.; Preusker, R.; Fischer, J.
Highlights: Thermal emission has been included in the successive orders of scattering (SOS) radiative transfer approach. The numerical implementation of the thermal expansion of SOS technique has been done in GRASP radiative transfer code. Radiance comparisons against DISORT reference code showed an mean uncertainty of − 0.003%. Different techniques for the optimization of the vertical discretization of temperature, scattering and absorption have been studied. The effects of polarization and the importance of the first order of approximation and the multiple scattering regime in TIR radiance calculations have also been investigated. Abstract: The Successive Orders of Scattering (SOS) approach [1] is one of the well known methods for solving the Radiative Transfer (RT) problem. Its efficiency in terms of speed and accuracy of computation was already demonstrated for scattering and absorbing atmospheres in Solar spectrum. Although there are no principle limitations to account for the emission processes, the application of the SOS method for atmospheres with thermal emission is not widely used yet. In this paper we present a SOS-based RT approach accounting for the full source function, which enables its application from the UV (UltraViolet) to the TIR (Thermal InfraRed) parts of the electromagnetic spectrum. The atmospheric vertical discretization in this extended SOS scheme is a key point in order to properly retain the scattering and emission processes. An analysis of different methodologies to perform this vertical discretization is presented. The numerical implementation has been included in GRASP (Generalized retrieval of Atmosphere and Surface Properties) RT code [2] . In comparison with the widely used code DISORT (DIScrete-ORdinatemethod for Radiative Transfer) [3], the developed SOS scheme achieves a mean accuracy of radiance calculation of − 0.005 K ( − 0.003%) expressed in terms of brightness temperature. Under the same configuration and vertically inhomogeneous atmospheric conditions, GRASP SOS RT is approximately eight times faster than DISORT. The analysis of the sensitivity of GRASP TIR SOS scheme to the number of layers and the effect of polarization are also investigated in the paper.